2014
DOI: 10.1007/s00213-014-3826-5
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of heroin-induced emotional dysfunction from psychomotor activation and physical dependence among inbred mouse strains

Abstract: Our results indicate that depressive-like behaviors emerge during heroin abstinence, whatever the severity of immediate behavioral responses to the drug. In addition, inbred mouse strains will allow studying several aspects of mood-related deficits associated with addiction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 74 publications
2
4
0
Order By: Relevance
“…Morphine abstinent mice displayed impaired direct social interaction, deficient nest building and compromised social preference, indicative of altered social behavior. These results match previous reports that protracted abstinence from chronic escalating opiate treatment produces social behavior deficits in rodents (Ayranci et al, 2014; Goeldner et al, 2011; Lutz et al, 2014; Zanos et al, 2014), as well as clinical reports describing social cognition/judgment deficits in patients under opioid maintenance (Johnson et al, 2014; McDonald et al, 2013). Alcohol, nicotine and THC abstinent mice also exhibited reduced social interaction.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Morphine abstinent mice displayed impaired direct social interaction, deficient nest building and compromised social preference, indicative of altered social behavior. These results match previous reports that protracted abstinence from chronic escalating opiate treatment produces social behavior deficits in rodents (Ayranci et al, 2014; Goeldner et al, 2011; Lutz et al, 2014; Zanos et al, 2014), as well as clinical reports describing social cognition/judgment deficits in patients under opioid maintenance (Johnson et al, 2014; McDonald et al, 2013). Alcohol, nicotine and THC abstinent mice also exhibited reduced social interaction.…”
Section: Discussionsupporting
confidence: 91%
“…These behavioral modifications differed across mouse strains (Ayranci et al, 2015) and were enhanced or reduced by genetic inactivation of delta and kappa opioid receptors, respectively (Lutz et al, 2014). We also tested gene expression for a large set of genes in the extended amygdala (EA), a key site contributing to hedonic and stress-related dysfunction in drug abuse.…”
Section: Introductionmentioning
confidence: 99%
“…Although the previous finding reported that acute mitragynine may have anxiolytic effects ( Farah et al, 2011 ; Hazim et al, 2014 ; Yusoff et al, 2016 ), our present data showed a lack of social interaction which suggests that mitragynine, regardless of the doses and LKD may induce anxiogenic effects in adolescent rats, affecting social behaviour in a novel environment. A growing literature investigating the effects of drug abuse on social behaviour in rodents demonstrates that drugs influence social behaviour ( Ayranci et al, 2014 ; Becker et al, 2017 ; Listos et al, 2022 ), especially in adolescence ( Kuhn, 2015 ). For instance, repeated alcohol exposure increases anxiety-like behaviour under social circumstances in adolescents but not in adult animals, as indicated by a decrease in social preference ( Varlinskaya and Spear, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…; Ayranci et al . ) and occurred before the emergence of despair‐like behavior at 7 weeks of abstinence (Lutz et al . ), suggesting that deficient sociability precedes mood disruption during ongoing heroin abstinence.…”
Section: Discussionmentioning
confidence: 99%